Effects of guanidinoacetic acid on growth performance, creatine metabolism and plasma amino acid profile in broilers. Issue 3 (2nd April 2019) - He, Dongting; Yang, Libin; Li, Juntao; Dong, Bing; Lai, Wenqing; Zhang, Liying
Abstract: The objective of this study was to assess the effects of guanidinoacetic acid (GAA) on growth performance, creatine deposition and blood amino acid (AA) profile on broiler chickens. In Exp. 1, a total of 540 one‐day‐old Arbor Acres male broilers (average initial body weight, 45.23 ± 0.35 g) were divided randomly into five treatments with six replicates of 18 chicks each. Broilers were fed corn–soybean meal‐basal diets supplemented with 0, 600, 800, 1, 000 or 1, 200 mg/kg GAA for 42 days respectively. Results showed that dietary GAA inclusion increased average daily gain (ADG) and improved gain‐to‐feed ratio (G:F) from 1 to 42 days ( p < 0.01). However, average daily feed intake was unaffected by dietary supplementation of GAA. As GAA inclusion increased, the contents of creatine in plasma and kidney were increased (linear, p < 0.01), while the contents of GAA and creatine in liver were decreased (linear, p < 0.01). Similarly, GAA supplementation was inversely related to concentrations of most essential AA in plasma. In Exp. 2, a total of 432 one‐day‐old Arbor Acres male broilers (average initial body weight, 39.78 ± 0.58 g) were divided randomly into four treatments with six replicates of 18 chicks each. Birds were fed a corn–soybean meal‐basal diet supplemented with 0, 200, 400 or 600 mg/kg GAA for 42 days respectively. Dietary inclusion of 600 mg/kg GAA significantly increased ADG and G:F of broilers ( p < 0.05). In conclusion, dietary supplementation of 600–1, 200 mg/kg GAA can effectively improve the growth performance in broiler chickens by affecting creatine metabolism and utilization efficiency of essential AA, and 600 mg/kg GAA is the minimum dose for improving performance.